Gambaran Penanaman Pendidikan Karakter pada Anak Usia Dini oleh Orang Tua di Dusun O5 Desa Perintis Kecamatan Rimbo Bujang Kabupaten Tebo - Ika Putri Irdani; Solfema Solfema (Universitas Negeri Padang, 2018)
The background of this research is early childhood in Hamlet 05 This Pioneer Village has polite behavior such as happy sharing, being gentle with friends, not quarreling when feeling unhappy, friendly, dislike to say dirty and like to share. This is presumably due to the low teaching skills of educators. This study aims to (1) describe the planting of character values from aspects of honesty (2) describing the planting of character values from the aspect of tolerance (3) describing the planting of character values from an independent aspect (4) describing the planting of character values from religious aspects (5) describing the planting of values characters from social care aspects in Dusun 05 Pioneer Village in Rimbo Bujang Subdistrict, Tebo District 30 people were made into the population. The technique used in sampling random sampling areas was taken forty-eight percent of respondents. The data collection technique uses questionnaires distributed to respondents, and data collection tools use questionnaires. Data analytical techniques with percentage formulas. So the results of the research are planting values of honesty, tolerance, independence, religiousness and social care in Hamlet 05 the Pioneer Village of Rimbo Bujang Subdistrict, Tebo District is categorized as high and good.Keywords: Character Education Planting